Association of farmers’ knowledge, attitude and practices with bovine brucellosis seroprevalence in Myanmar - Su Su Hlaing; Satoko Kubota; Kohei Makita; Ye Tun Win; Hnin Thidar Myint; Hiroichi Kono (Animal Bioscience, 2024)
Objective This study aimed to identify the relationship between bovine brucellosis prevalence, farmers’ knowledge, attitude, practice (KAP), and social factors on migratory draft cattle and smallholder dairy farms in the central dry zone of Myanmar. Methods This cross-sectional study was conducted on 54 migratory and 38 dairy cattle farms between August 2020 and February 2021. A structured questionnaire was used to identify farmers’ behaviors. Bulk milk was sampled and tested using indirect enzyme-linked immunosorbent assay (I-ELISA). STATA 17 was used for all the analyses. Results Migratory cattle farms had a higher farm level brucellosis prevalence (14.8%) than dairy farms (2.6%; χ2 = 3.75; df = 1; p = 0.05). Only 2.8% of the farmers had knowledge about brucellosis, while 39.1% and 41.6% had attitudes and farm practices with respect to brucellosis, respectively in the study area. Socio-economic attribute of training in animal husbandry (p<0.01), raising system (p<0.01), practice of separating the aborted cow (p<0.01) were negatively associated to brucellosis. The overall farm level brucellosis prevalence was strongly associated with cattle herd size (p = 0.01), free movement grazing practices (p<0.01), practice of self-removal of placental debris without using personal protective equipment (p<0.01) and farmers’ attitudes towards eating cow placenta debris (p<0.01). Conclusion Farmers had little knowledge of brucellosis. Attitudes and practices differed significantly between migratory and dairy farmers. Training and extension programs are necessary to make farmers aware of their KAP situation since livestock migration and the custom of eating cow placental debris contribute to the spread of brucellosis. Persistent efforts are required to reduce the adverse effects of brucellosis. Therefore, the study suggests that a feasible control intervention and public awareness campaigns need to be conducted regarding methods of preventing human exposure to brucellosis.